Pengaruh Kualitas Pelayanan Terhadap Loyalitas Konsumen Di Hotel Best Western Plus Kemayoran, Jakarta - Dadang Kurnia Abdurrahman; Sri Fajar Ayuningsih (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
This study aimed to analyze the effect of service on customer loyalty at the Best Western Plus Hotel Kemayoran. The research method used is a quantitative research approach. Data collection techniques to test hypotheses through a questionnaire addressed to 50 respondents who use the services of the Best Westen Plus Hotel Kemayoran. And equipped with making observations and literature study. The respondent sample data collection was carried out using an accidental sampling technique. The data analysis method used consists of validity test, reliability test, standard linear analysis test with t test, product moment correlation coefficient, and determination coefficient. The results obtained from the analysis of SPSS statistical data processing and hypothesis testing, namely the correlation coefficient between the service quality variable (X) and the customer loyalty variable (Y) is significant because it is between 0.5 <r< 075. Based on the results of the t-test analysis, the results are greater than the table, namely 2.604> 2.01. This figure shows that H0 is rejected and H1 is accepted, which means that the service quality variable (X) has a significant effect on customer loyalty (Y).